Role of the Cation-Chloride-Cotransporters in Cardiovascular Disease - Meor Azlan, Nur Farah (Cells, 2020)
The SLC12 family of cation-chloride-cotransporters (CCCs) is comprised of potassium chloride cotransporters (KCCs), which mediate Cl(−) extrusion and sodium-potassium chloride cotransporters (N[K]CCs), which mediate Cl(−) loading. The CCCs play vital roles in cell volume regulation and ion homeostasis. The functions of CCCs influence a variety of physiological processes, many of which overlap with the pathophysiology of cardiovascular disease. Although not all of the cotransporters have been linked to Mendelian genetic disorders, recent studies have provided new insights into their functional role in vascular and renal cells in addition to their contribution to cardiovascular diseases. Particularly, an imbalance in potassium levels promotes the pathogenesis of atherosclerosis and disturbances in sodium homeostasis are one of the causes of hypertension. Recent findings suggest hypothalamic signaling as a key signaling pathway in the pathophysiology of hypertension. In this review, we summarize and discuss the role of CCCs in cardiovascular disease with particular emphasis on knowledge gained in recent years on NKCCs and KCCs.